2021
DOI: 10.1002/biot.202100320
|View full text |Cite
|
Sign up to set email alerts
|

Virus inactivation at moderately low pH varies with virus and buffer properties

Abstract: Background: Virus inactivation is a critical operation in therapeutic protein manufacturing. Low pH buffers are a widely used strategy to ensure robust enveloped virus clearance. However, the choice of model virus can give varying results in viral clearance studies. Pseudorabies virus (SuHV) or herpes simplex virus-1 (HSV-1) are frequently chosen as model viruses to demonstrate the inactivation for the herpes family.Results: In this study, SuHV, HSV-1, and equine arteritis virus (EAV) were used to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Additionally, viral inactivation is often sensitive to environmental factors and choice of virus strain. For example, recent studies have found that the efficacy of low-pH viral inactivation depends on the virus strain and the buffering agent used …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, viral inactivation is often sensitive to environmental factors and choice of virus strain. For example, recent studies have found that the efficacy of low-pH viral inactivation depends on the virus strain and the buffering agent used …”
Section: Resultsmentioning
confidence: 99%
“…While a highly acidic pH (<3.6) effectively inactivates the xenotropic murine leukemia virus, 83 a pH of 4.0 has little effect on the equine arteritis virus. 84 Conventionally, enveloped viruses are rendered inactive at high aqueous temperatures due to the denaturation of their proteins. In reagent-grade water, the time for a 99% reduction of the transmissible gastroenteritis population at 4 °C (220 days) is significantly longer than at 25 °C (22 days).…”
Section: Release Of Enveloped Viruses Into Liquidsmentioning
confidence: 99%
“…Typically, a low pH treatment is used to inactivate enveloped viruses. While a highly acidic pH (<3.6) effectively inactivates the xenotropic murine leukemia virus, a pH of 4.0 has little effect on the equine arteritis virus . Conventionally, enveloped viruses are rendered inactive at high aqueous temperatures due to the denaturation of their proteins.…”
Section: Environmental Transmission Of Enveloped Virusesmentioning
confidence: 99%
“…Viruses are exposed to a variety of other degradation risks when preserved including freeze–thaw damage, pH changes, surface adsorption, shear stress, and oxidative denaturation. For example, the crystallization of buffers during the freezing process can lead to pH changes, especially in sodium phosphate buffers [ 7 ], where both overly high and overly low pH can cause virus denaturation [ 8 , 9 ]. In addition, low pH values cause viral aggregation, which may cause irreversible changes by viral denaturation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%